Peculiarities of microstructure of the suprarenal glands of rabbits with different types of autonomic tone - Zakrevska, M. V.; Tybinka, A. M. (Regulatory Mechanisms in Biosystems, 2019)
The article investigates the structure of the suprarenal (adrenal) glands of male rabbits (Oryctolagus cuniculus), in which, on the basis of electrocardiographic and variational-pulsometric studies, different types of autonomic tone were observed. This allowed the animals to be divided into three groups: 1) sympathicotonic rabbits; 2) normotonic rabbits; 3) parasympathicotonic rabbits. The animals of the first two groups were characterized by almost the same body weight, while weight of the rabbits of the third group was slightly higher. After euthanasia, the suprarenal glands were extracted for histological and histochemical analyses. Morphometric study of histopreparations revealed that in the normotonic rabbits the thickness of the zona glomerulosa and zona fasciculata of the suprarenal glands were of average sizes, and the area of the medulla was the smallest. The parasympathicotonic rabbits had the thickest zona glomerulosa and greatest area of the medulla, but the thinnest zona fasciculata. The sympathicotonic rabbits were observed to have the greatest thickness of the zona fasciculata of the suprarenal glands, the area of the medulla was of average values, and the thickness of the zona glumerulosa was of minimum value. The type of autonomic tone also manifests in the saturation of each of the zones with cells. The normotonic rabbits were observed to have the highest number of cells per area of 1,000 µm² in the zona fasciculata and the medulla, sympathicotonic rabbits – in the zona glomerulosa and zona reticularis, and in parasympathicotonic rabbits this parameter had average or lowest values in all the zones. The sizes of cells and their structural parts were characterized on the basis of nuclear-cytoplasmic ratio. In the zona fasciculata and medulla this parameter was highest among parasympathicotonic rabbits, and lowest in sympathicotonic rabbits. In the zona glomerulosa, almost equal values were observed in the normotonic and parasympathicotonic rabbits, while being reliably lower in sympathicotonic rabbits. By the value of nuclear-cytoplasmic ratio in the zona reticularis, the normotonic rabbits dominated, followed by the sympathicotonic animals, and the parasympathicotonic rabbits had the lowest parameters.